DAYA TARIK TAMAN WISATA AROMA PECCO KAYU ARO KABUPATEN KERINCI - Natalia, Dewi; Yuliana, Yuliana; Pramudia, Heru (Journal of Home Economics and Tourism, 2017)
This Research aims to understand Attraction of Aroma Pecco tourism Kayu Aro. The kind of research is descriptive research with qualitative data. data collection techniques was carried out by using observation and interviews. In this research involving informants as many as 2 people management of Aroma Pecco tourism KayuAro using purposive sampling technique and 3 people of community and 4 people of Visitor using snowball sampling technique.Analysisdata by means of the reduction of the data , presentation of data and retrieval of conclusion. Result in this research indicates Aroma Pecco Tourism Attraction KayuArothe aspect of 1) tourist attraction has specific characteristic which obtained from natural source namely in the form of small lake which is located in the middle of the broad garden tea with in surrounded the trees, so the visitor can feel the air that was cool and fresh as well as to be supported by the strategic place because the area tourist Aroma Pecco destination located on roadside main traffic between town and district. An entertainment that held once a year , from 2) accessibilities of the distance traveled which is not too far from the center of the city that is 45 km and time 1.5 hour with the appropriate fee and the traffic being facile when normal days but there is congestion at the time of the holiday , 3) amenities the availability of the lack of facilities and infrastructure that could support tourism activities and 4) ancillary service the unavailability of store merchandise and lack of a recreational facility.Keyword: Tourism Attraction, Tourism Object